Final report on plasma ctDNA T790M monitoring during EGFR-TKI treatment in patients with EGFR mutant non-small cell lung cancer (JP-CLEAR trial). (22nd March 2022) - Naka, Go; Yokoyama, Takuma; Usui, Kazuhiro; Ishida, Hiroo; Kishi, Kazuma; Uemura, Kohei; Ohashi, Yasuo; Kunitoh, Hideo
Abstract: Osimertinib is active against T790M-positive epidermal growth factor receptor mutant non-small cell lung cancer. We enrolled 122 sensitive epidermal growth factor receptor mutant non-small cell lung cancer patients who were planned to receive or were receiving first-/second-generation epidermal growth factor receptor tyrosine kinase inhibitors without disease progression and monitored plasma T790M every 1–2 months using the cobas® EGFR Mutation Test v2. We previously reported the concordance between T790M status in plasma and tissue. This is the final report on the sensitivity of plasma T790M and the efficacy of sequential osimertinib. The sensitivity was 21.1% (95% confidence interval: 6.1–45.6%). The best overall response was 25.0% (95% confidence interval: 9.8–46.7) in the plasma T790M-positive group and 28.6% (95% confidence interval: 8.4–58.1) in the plasma T790M-negative but tissue T790M-positive group. Median progression-free survival was 7.9 months (95% confidence interval: 4.7–17.5) for the former and 4.4 months (95% confidence interval: 3.0–N.E.) for the latter, with no statistically significant difference ( P = 0.74). Abstract : In our study, with regular monitoring of plasma circulating tumor DNA (ctDNA) T790 in daily practice, there was no statistically significant difference in progression-free survival between the plasma ctDNA-positive and ctDNA-negative groups.